In-migration and dilution of community social capital - Julie L. Hotchkiss; Anil Rupasingha (Federal Reserve Bank of Atlanta, 2018)
Consistent with predictions from the literature, we find that higher levels of in-migration dilute multiple dimensions of a community's level of social capital. The analysis employs a 2SLS methodology to account for potential endogeneity of migration.
Keywords: R23; D71; C36; C38; 330; social capital; migration; decennial census; social capital community benchmark survey; nonpublic data; simultaneous equations; endogeneity; factor analysis